Detailed Study on the Mechanical Properties and Activation Energy of Natural Rubber/Chloroprene Rubber Blends during Aging Processes - Quang Nguyen Trong; Hung Dang Viet; Linh Nguyen Pham Duy; Chuong Bui; Duong Duc La (Journal of Chemistry)
Selection of a suitable thermal aging process could render desirable mechanical properties of the rubbers or blended rubbers. In this work, the effect of the aging processes on the mechanical properties and activation energies of natural rubbers (NR) and NR/chloroprene rubbers (CR) blends with low CR contents (5–10%) was investigated. Three aging processes including heat aging (at 110°C for 22 hours), mechanical aging (under dynamic loading to 140% strain for 16000 cycles), and complex aging (heat and mechanical aging) were studied. The results revealed that the compatibility of CR in natural rubber matrix had a significant effect on the dynamic properties of the blended rubber and negligible effect on the static properties. The changes in activation energies of the blended rubber during aging processes were calculated using Arrhenius relation. The calculated changes (ΔUc, ΔUd, and ΔUT) in activation energies were consistent with the results of mechanical properties of the blended rubber. Interestingly, the change in activation energies using complex aging conditions (ΔUc) was mostly equal to the total changes in activation energies calculated separately from heat aging (ΔUT) and mechanical aging (ΔUd) conditions. This indicates that, in complex aging conditions, the heat and dynamic loading factors act independently on the properties of the blended rubber.